Importance of Integrating Effective Teaching Methods in Business English Classroom - Tamar Dolidze; Anna Abesadze; Brandon Harding; Paola Clara Leotta (European Scientific Journal, ESJ, 2022)
The paper will highlight the importance of integrating effective teaching methods in teaching English for Specific Purposes, in particular Business English. Based on the survey, where 48 BE instructors participated from different countries, the article will demonstrate the significance of Lexical Approach, Task-Based and Project-based Learning by evaluating the outcomes of integrating them in teaching practice and beyond. The results once again confirmed the hypothesis. The survey consisted of both open and close-ended questions and aimed at voicing the opinion of BE Course Instructors globally. The target audience was exposed to the above-mentioned teaching methods. At the same time, the survey provides recommendations for beginner BE Lecturers on how to ensure maximal approximation to the authentic environment via practicing most useful teaching methods and making the learning process more result-driven, engaging and enjoyable.